PEMBUATAN MINUMAN HERBAL KAYU SECANG UNTUK MENINGKATKAN PEREKONOMIAN DAN KESEHATAN MASYARAKAT BLOK GOMBANGAN, DESA SANCA, GANTAR, INDRAMAYU - Abdur Rahim; Siti Ngainnur Rohmah; Khisma Dina Khalisa; Indah Hafizhah; Muhamad Ramdan; Firdaus Al Kamil; Shabna Dafita; Suanda Suanda (LPPM Universitas Bina Bangsa, 2023)
Covid 19 has changed the fabric of social life. People who are essentially social beings are prevented from interacting with each other and consequently in their efforts to fulfill the basic needs of human life. To avoid the possibility of contracting Covid 19, people need to adjust the way they interact with each other. But on the other hand, people have to work to provide for themselves and their families. The community of Sanca Blok Gombangan Village cannot be separated from the impact of Covid 19. This service adopts the ABCD method, which is a service that focuses on improving living standards by utilizing assets owned by the community. Local assets are sometimes neglected and not used optimally due to people's ignorance. Therefore, this method was adopted to reintroduce existing assets to the community so that they can be used to improve the standard of living. Based on our research, we found that various plant resources, including the sappan tree (Caesalpinnia sappan L), have not been used optimally. Various studies have shown that sap fruit can be processed into hot drinks that are delicious and healthy. Based on this, the residents of Sanca Village were taught how to make herbal drinks from turtle trees and how to sell them to improve the health and economy of Sanca Village